The adaptation of acoustic data from commercial fishing vessels in resource assessment and ecosystem monitoring - Melvin, G.; Kloser, Rudy; Honkalehto, T. (Elsevier BV, 2016)
© 2015 Published by Elsevier B.V.The collection of scientific data from commercial fishing vessels will play an important role in the future assessment of fish stocks and ecosystem monitoring. Currently fishing vessel acoustic data collections range from fully structured random/systematic surveys to the ad hoc search patterns of pelagic vessels during standard fishing operations, and are used primarily in single species stock assessment. To effectively use these data a good understanding of the data collection methods, analytical procedures, and the limitations of the data is required. Consideration of the limitations and interpretation of the data are a major factor in evaluating the validity of the outputs, the uncertainties associated with the data and the acceptance of the results by the scientific community. In this paper we provide 3 case studies of how acoustic data from commercial fishing vessels are being used to provide information on fish resources and advice to management. We categorize a fishing trip into 3 phases: transiting, searching, and fishing, and we discuss the attributes and limitations of data collected during each phase. Examples of current fishing vessel data collections and their application in resource assessment and environmental monitoring are presented. In addition, we explore opportunities for acoustics to support broad-scale ecosystems monitoring, without interfering with the day-to-day operations of the vessels.